16S rRNA Gene Amplicon Sequencing Data of the Iron Quadrangle Ferruginous Caves (Brazil) Shows the Importance of Conserving This Singular and Threatened Geosystem - Lemes, Camila G. C.; Villa, Morghana M.; Felestrino, Érica B.; Perucci, Luiza O.; Assis, Renata A. B.; Cordeiro, Isabella F.; Fonseca, Natasha P.; Guerra, Lara C. C.; Caneschi, Washington L.; Moraes, Lauro Â. G.; do Carmo, Flávio F.; Kamino, Luciana H. Y.; et al. (Diversity (Basel), 2021)
The Iron Quadrangle (IQ) is one of the main iron ore producing regions of the world. The exploitation of its reserves jeopardizes the high biological endemism associated with this region. This work aimed to understand the diversity and bacterial potential associated with IQ caves. Floor and ceiling samples of seven ferruginous caves and one quartzite cave were collected, and their microbial relative abundance and diversity were established by 16S rRNA gene amplicon sequencing data. The results showed that ferruginous caves present higher microbial abundance and greater microbial diversity compared to the quartzite cave. Many species belonging to genera found in these caves, such as Pseudonocardia and Streptacidiphilus, are known to produce biomolecules of biotechnological interest as macrolides and polyketides. Moreover, comparative analysis of microbial diversity and metabolic potential in a biofilm in pendant microfeature revealed that the microbiota associated with this structure is more similar to the floor rather than ceiling samples, with the presence of genera that may participate in the genesis of these cavities, for instance, Ferrovum, Geobacter, and Sideroxydans. These results provide the first glimpse of the microbial life in these environments and emphasize the need of conservation programs for these areas, which are under intense anthropogenic exploration.